1987
DOI: 10.1161/01.hyp.9.2_pt_2.ii53
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy in hypertension. Prevalence and relationship to pathophysiologic variables.

Abstract: SUMMARY In less than a decade since development of echocardiographic measurement of left ventricular muscle mass, studies using this technique have provided considerable information about the prevalence and pathophysiology of left ventricular hypertrophy in human hypertension. Increased left ventricular mass has been found in a significant minority of patients with systemic hypertension, with the exact prevalence dependent both on how a population is selected and on the sex, race, and possibly age composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 57 publications
3
51
1
1
Order By: Relevance
“…The prevalence of echocardiographic LV hypertrophy of 34.3% was similar to the rates found in other populations with hypertension. 26 Almost all the subjects with hypertension were receiving antihypertensive treatment, but no participant was receiving spironolactone, a diuretic that acts by antagonising the effect of aldosterone. The average family size and number of generations per family was seven members (range 3 -27) and two generations (range 2 -4), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of echocardiographic LV hypertrophy of 34.3% was similar to the rates found in other populations with hypertension. 26 Almost all the subjects with hypertension were receiving antihypertensive treatment, but no participant was receiving spironolactone, a diuretic that acts by antagonising the effect of aldosterone. The average family size and number of generations per family was seven members (range 3 -27) and two generations (range 2 -4), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In hypertensive patients irrespective of age, LVH is an adaptation to an increased end systolic wall stress and by thickening of LV walls leads to its normalisation. 2,11 In a stepwise multiple analysis of a very heterogeneous population of 171 hypertensive patients, we demonstrated that age was an independent determinant of posterior and septal wall thickness and of LV mass. 11 Posterior wall thickness increased by about 25% between the 2nd and 7th decade of life, and the ratio of radius to wall thickness declined, indicating LVH of the concentric type.…”
Section: Lvh and Hypertensionmentioning
confidence: 88%
“…Various studies have documented an increase in wall thickness with age in the presence of unchanged chamber volume. [1][2][3] In addition to the increased size of the myocytes, the aging heart is characterised by a high rate of degenerative age-associated findings such as lipid deposition, tubular dilatation and decreased mitochondrial oxidative phosphorylation. 3,4 Concomitantly, the amount of elastic tissue, collagen and fat increases.…”
Section: Left Ventricular Hypertrophymentioning
confidence: 99%
“…The LV diameter in end diastole, interventricular septum (IVSd) and LV posterior wall thickness in end diastole were measured from the M-mode readings. LV mass (LVM) was calculated by the formula of Devereux 15 and was indexed to the allometric power of height (LVM/Ht 2.7 ).The LV ejection fraction was estimated by the use of a modified version of Simpson's biplane method.…”
Section: Two-dimensional and M-mode Echocardiographymentioning
confidence: 99%